The Development of International and National Sovereignty of the Law of the Sea in the Perspective of Philosophical Analysis - Izziyana, Wafda Vivid; Matompo, Osgar Sahim; Rimbawan, Andhika Yuli (Jurnal Justiciabelen, 2023)
International law of the sea is one of the branches of international law that has experienced significant development in the last 50 years and will always develop dynamically from time to time. This research uses doctrinal legal methods, data analysis techniques are carried out qualitatively with deductive thinking patterns. Data processing begins with editing, classification, verification, analysis, and conclusions. The results of this research explain the development of the sovereignty of the provisions of international law of the sea began in 1930 when developed countries began to have the ability to explore and exploit natural resources, especially oil in the sea. Before the holding of the International Law of the Sea Conference or commonly called the First United Nations Conference on the Law of the Sea (UNCLOS I) in 1958, the use of the sea was regulated by international customary law. Furthermore, UNCLOS II in 1960 formulated a resolution on the need for certain technical methods in terms of fisheries, and the proliferation of sovereignty claims over sea areas submitted by new countries, regulating sea-bed with the concept of common heritage of mandkind and the decision to hold UNCLOS III in 1974-1982, UNCLOS 1982 regulates the division of maritime zones with their respective legal regimes and, which is very revolutionary in the development of international law of the sea is the recognition of the concept of island states in Chapter IV of UNCLOS 1982. The development of international maritime law sovereignty greatly influenced national maritime law policy, Indonesia poured the Juanda Declaration into the form of regulations, namely Law No. 4 / Prp / 1960 concerning Indonesian Waters also emphasizes economic factors and the need to preserve biological and non-biological natural resources. other laws and regulations that support the Indonesian water system Law No.4 / Prp / 1960. include Government Regulation No. 8/1962 (PP 8/1962) concerning the right of peaceful passage and Law no. 1/1973 (Law 1/1973) concerning the continental shelf. This forces foreign vessels to notify the Indonesian government of their presence. Border agreements with neighboring countries indirectly support the 'archipelagic state concept' proposed by Indonesia. This will strengthen the existence of the 'archipelagic state concept.